Nursing interventions with drains in the perioperative period: An integrative review (Research, Society and Development, 2020)
The management of surgical drains is a common practice in perioperative nursing care, so it is necessary to analyze the interventions of these professionals and their approximation with standardized language systems that help in a more effective practice. Objective:To analyze which nursing interventions are performed in the perioperative period regarding the management of drains. Method:Integrative review that searched the CINAHL, PuBMed, LILACS and Scopus databases, publications that answered the question: What are the nursing interventions in the management of drains in the perioperative period? Results:Ninety (90) publications were collected, but only eight (08) met the eligibility criteria. Among them, the following interventions were highlighted: cleaning and dressing change; coverage assessment carefully with materials and techniques; emotional support; physical exam; Health education; patient positioning; pain control; signs of infection; secretion control and removal of the device. Conclusion:It is noted that there is a distance between assistance and the interventions proposed by the NIC. Thus, Nursing must still walk in order to solve this gap.